Delta-8 gummies causing visual snow: a case report - Vaphiades, Michael S. (Frontiers in Ophthalmology, 2024)
A 26-year-old man developed visual snow syndrome (VSS) after consuming a little less than ½ of a delta-8 gummy (estimated at 4 mg of delta-8 tetrahydrocannabinol). I discuss secondary VSS and hallucinogen persisting perception disorder (HPPD) and alert the clinician who evaluates patients with VS and VSS, to ask about delta-8 gummies as an etiology of secondary VSS.